Impact of School Closure Due to COVID-19 on the Social-Emotional Skills of Japanese Pre-school Children - Doi, Satomi; Miyamura, Keitaro; Isumi, Aya; Fujiwara, Takeo (Frontiers in Psychiatry, 2021)
Objective: This study examines the impact on the social-emotional skills of Japanese pre-school children from downsizing of school activities in conjunction with voluntary school closures due to the first wave of COVID-19, in 2020. Methods: Participants included 32 children aged 4–5 years old from three pre-schools in Tokyo, Japan, where strict lockdown was not implemented and voluntary school closure was recommended. Child social-emotional skills was assessed by classroom teachers using Devereux Student Strengths Assessment mini (DESSA-mini) three times: November 2019, January 2020 (before the COVID-19), and March 2020 (during the first COVID-19 wave). All pre-schools implemented voluntary school closures from March 2nd, and two schools (school A and B) canceled school recitals, while one school (school C) allowed for it to be held on March 4th, with precautions in place to prevent the spread of infection. Repeated measures ANOVA were performed to examine the difference between the T scores of the DESSA-mini three pre-schools before and during the COVID-19 pandemic. Results: In school C, children showed stable T scores of the DESSA-mini, whereas children in school A and B showed lower T scores of the DESSA-mini during COVID-19 than before it started. The interaction effects between time and pre-schools were found (F = 7.05, p < 0.001). Conclusion: Our findings suggest that school recitals in pre-schools were important to maintaining children's social-emotional skills during the COVID-19 pandemic.